The tadpole of Chiasmocleis schubarti Bokermann, 1952 (Amphibia, Anura: Microhylidae) - Santos, Marcus Thadeu T.; Pezzuti, Tiago L.; Leite, Felipe S. F.; Garcia, Paulo C. A. (Zootaxa, 2015)
The genus Chiasmocleis Méhely comprises 29 species distributed from Panama to tropical South America clustered in five clades: C. albopunctata, C. bassleri, C. hudsoni, C. shudikarensis and C. ventrimaculata (Peloso et al. 2014). Chiasmocleis schubarti Bokermann belongs to the C. albopunctata clade, which also includes C. alagoana Cruz, Caramaschi, and Freire, C. albopunctata (Boettger), C. capixaba Cruz, Caramaschi, and Izecksohn, C. lacrimae Peloso, Sturaro, Forlani, Gaucher, Motta, and Wheeler, C. leucosticta (Boulenger), and possibly other morphologically and/or molecularly related species that have never been included in a phylogenetic analysis in a broader context (e.g., C. atlantica Cruz, Caramaschi and Izecksohn, C. cordeiroi Caramaschi & Pimenta, C. crucis Caramaschi & Pimenta, C. gnoma Canedo, Dixo and Pombal and C. mantiqueira Cruz, Feio and Cassini) (Cruz et al. 2007). Within these species, C. alagoana, C. albopunctata, C. lacrimae, C. leucosticta and C. mantiqueira have their larval forms described (Wogel et al. 2004; Nascimento & Skuk 2006; Oliveira-Filho & Giaretta 2006; Langone et al. 2007; Santana et al. 2012).